2023
DOI: 10.1039/d3ra01542d
|View full text |Cite
|
Sign up to set email alerts
|

Salazinic acid attenuates male sexual dysfunction and testicular oxidative damage in streptozotocin-induced diabetic albino rats

Abstract: Protective effects of salazinic acid on male spermatogenic dysfunction in STZ-induced diabetic albino rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(82 reference statements)
0
0
0
Order By: Relevance
“…Neurodegenerative diseases pose significant health challenges that impose substantial cost burdens on ageing and elderly populations [39]. The existing literature mainly indicates that individuals with AD commonly have impairment in cholinergic activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Neurodegenerative diseases pose significant health challenges that impose substantial cost burdens on ageing and elderly populations [39]. The existing literature mainly indicates that individuals with AD commonly have impairment in cholinergic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Scopolamine-induced dementia has been widely employed in assessing putative therapeutic interventions for treating AD [39,48]. The study conducted by MT et al [70] demonstrated that the administration of scopolamine in mice brains impacts the expression of many genes related to muscarinic receptor signaling pathways, apoptosis, and cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations